Local corticosteroid injection in iliotibial band friction syndrome in runners: a randomised controlled trial. Issue 3 (21st May 2004) - Gunter, P; Schwellnus, M P
Abstract : Objective: To establish whether a local injection of methylprednisolone acetate (40 mg) is effective in decreasing pain during running in runners with recent onset (less than two weeks) iliotibial band friction syndrome (ITBFS). Methods: Eighteen runners with at least grade 2 ITBFS underwent baseline investigations including a treadmill running test during which pain was recorded on a visual analogue scale every minute. The runners were then randomly assigned to either the experimental (EXP; nine) or a placebo control (CON; nine) group. The EXP group was infiltrated in the area where the iliotibial band crosses the lateral femoral condyle with 40 mg methylprednisolone acetate mixed with a short acting local anaesthetic, and the CON group with short acting local anaesthetic only. The same laboratory based running test was repeated after seven and 14 days. The main measure of outcome was total pain during running (calculated as the area under the pain versus time graph for each running test). Results: There was a tendency (p  =  0.07) for a greater decrease in total pain (mean (SEM)) during the treadmill running in the EXP group than the CON group tests from day 0 (EXP  =  222 (71), CON  =  197 (31)) to day 7 (EXP  =  140 (87), CON  =  178 (76)), but there was a significant decrease in total pain during running (p  =  0.01) from day 7 (EXP  =  140 (87), CON  =  178 (76)) to day 14 (EXP  =  103 (89), CON  =  157 (109)) in the EXP group compared with the CON group. Conclusion: Local corticosteroid infiltration effectively decreases pain during running in the first two weeks of treatment in patients with recent onset ITBFS.